Diseño de actividades utilizando las simulaciones PhET para el aprendizaje activo de Química General con los estudiantes de segundo semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología. - Agualsaca Guallán, Alex Dario (2025)
The research primarily focused on the constant updates of PhET simulations, necessitating the development of activities that incorporated active learning. The worksheets were designed to promote active student participation through exploration, critical thinking, hypothesis formulation, and reflection. A quantitative research approach was employed, utilizing a non-experimental and descriptive design, as it aimed to observe and describe the impact of using simulations without manipulating variables. Additionally, activities were developed and integrated into a structured didactic guide to facilitate their use in the classroom. The literature review drew on various academic sources, including books, scientific journals, articles, and university repositories, to provide theoretical support. The guide was evaluated through a survey applied to a population of 39 students, who provided feedback on its clarity, usefulness, and effectiveness. The results obtained reflect that the use of PhET simulations, in combination with active learning strategies, facilitates the understanding of abstract concepts, stimulates interest in the subject, and improves the development of scientific skills in students. It is recommended to incorporate worksheets based on PhET simulations into the development of didactic guides, as these activities help students learn in an organized manner, eliminating the need to search through browsers, and are useful for planning pedagogical use.